Nursing Care for Orthopedic Patients in Aeromedical Evacuation - Mongkol, Junyaporn; Choocherd, Sirinan; Kaukeaw, Aroontree (Journal of The Royal Thai Army Nurses, 2023)
Bone, muscle, and joint injuries are emergency conditions that can cause harmful complications in the patient’s life. Aeromedical evacuation plays an essential role in helping patients receive timely medical care in a high-capacity hospital to treat them to reduce complications. Therefore, aeromedical evacuation is a considerable challenge as it transportation under limited of narrow aircraft, less of personnel for safety flight and it may be an aircraft emergency all the time so it requires proper patient selection, preparation, and appropriate nursing care throughout the air transport period. For this reason, flight nurses who take care of the patient while transporting must have knowledge and skills in aviation medicine nursing in order to provide nursing care to orthopedic patients correctly and suitably.